(untitled) (Scientific journal of the Fergana State University, 2025)
This article presents the results of a comparative analysis of predatory bugs of the family Reduviidae studied in Uzbekistan based on literature data. In addition, scientific research conducted in various regions of southern Uzbekistan (Muborak, Nishon, Karshi, and Yakkabog in Kashkadarya Region, as well as Termez and Sariosiyo in Surkhandarya Region) recorded 7 species of predatory bugs belonging to 4 subfamilies and 7 genera of the family Reduviidae. The article also provides information on the degree of study of predatory bugs in different regions of Uzbekistan and their bioecological characteristics.